The EU as a Coherent (Cyber)Security Actor? - Carrapiço, Helena (2017)
The last three decades have seen the development of the European Union (EU) as a security actor. The transnational character of the security threats and the challenges identified by the EU have led to progressive integration between internal and external security concerns. These concerns have often led to calls for greater coherence within EU security policies. The literature, however, indicates that this need for coherence has, so far, not been systematically operationalized, leading to a fragmented security field. This article has two main aims: To devise a framework for the analysis of the EU’s coherence as a security actor, and to apply it to the cybersecurity field. By focusing on EU cybersecurity policy, this article will explore whether the EU can be considered a coherent actor in this field or whether this policy is being implemented according to different and unco-ordinated rationales.